Fall from grace [large type] - Patterson, Richard North (Thorndike Press large print core series., 2012)
Adam Blaine arrives at the funeral of his estranged father, Ben Blaine, a famous and charismatic writer who left behind him a string of secret legal and financial arrangements. Using his training as a CIA operative, Adam seeks to find the truth of his father's death, even if it means exposing one or more of his own family members as the killer and discovering secrets about himself that he was never supposed to know.